Development of digital technologies for agribusiness (Journal of Economic Research & Business Administration, 2021)
The contribution of small and medium-sized businesses to the Kazakhstan’s GDP is just over 27%,and the share of innovative enterprises in this sector of the economy is just over 0.98%. Currently theshare of SMEs in Japan’s GDP is 95 percent, the United States – 80%, Western Europe – 60%. In orderto be more economically stronger and independent of oil bondage for national economy is advised toincrease SMEs proportion.The primer goal of this publication to raise concerns and recommendations on boosting digital literacywithin SMEs owners, particularly in agribusiness and government structures. It is undeniable thatwithout interconnection or as they say government-private partnership such capital needed processeslike digitalization of business processes for both public and private success would not be seen.The further development of digitalization in agriculture is hindered not by the availability or weakdevelopment of Internet connections, as well as the lack of local systems for spreading knowledge andtraining specialists in the use of digital tools.For various solutions in the process of the study appropriate qualitative research methods have beenused: monographic, analysis and synthesis, logical and abstractive constructional, etc.In this paper ongoing digitalization processes from government of Kazakhstan in general was presented,application of this process to one of the most important industry (agriculture) is shown, problemsfor further advancement of digitalization of economy is pointed and some developments were made.The object of research is the processes and tools of digitalization of decision-making used by smalland medium-sized agribusiness in Kazakhstan.The findings of this study contribute to preparation and advancing of conceptual development ofdigitalization for business-government relationships, therefore increasing competitiveness of industryand economy intact.Key words: digitalization, new technologies, digital solutions, small and medium business, IT solutions,IT platforms.